Transcription factor binding at Ig enhancers is linked to somatic hypermutation targeting. Issue 3 (19th December 2019) - Dinesh, Ravi K.; Barnhill, Benjamin; Ilanges, Anoj; Wu, Lizhen; Michelson, Daniel A.; Senigl, Filip; Alinikula, Jukka; Shabanowitz, Jeffrey; Hunt, Donald F.; Schatz, David G.
Abstract: Secondary diversification of the Ig repertoire occurs through somatic hypermutation (SHM), gene conversion (GCV), and class switch recombination (CSR)—three processes that are initiated by activation‐induced cytidine deaminase (AID). AID targets Ig genes at orders of magnitude higher than the rest of the genome, but the basis for this specificity is poorly understood. We have previously demonstrated that enhancers and enhancer‐like sequences from Ig genes are capable of stimulating SHM of neighboring genes in a capacity distinct from their roles in increasing transcription. Here, we use an in vitro proteomics approach to identify E‐box, MEF2, Ets, and Ikaros transcription factor family members as potential binders of these enhancers. ChIP assays in the hypermutating Ramos B cell line confirmed that many of these factors bound the endogenous Igλ enhancer and/or the IgH intronic enhancer (Eμ) in vivo. Further investigation using SHM reporter assays identified binding sites for E2A and MEF2B in Eμ and demonstrated an association between loss of factor binding and decreases in the SHM stimulating activity of Eμ mutants. Our results provide novel insights into trans‐acting factors that dictate SHM targeting and link their activity to specific DNA binding sites within Ig enhancers. Abstract : An in vitro mass spectrometry based approach uncovers transcription factors that bind to Ig enhancers capable of targeting SHM known as diversification activator (DIVAC) sequences. Binding of transcription factors to these sequences is shown to be linked to their capability to target somatic hypermutation.